A Computationally Efficient 3D Mathematical Model of a Molybdenum Batch-Reheating Furnace⁎, ⁎⁎. Issue 2 (2018) - Roetzer, Florian; Aschauer, Alexander; Steinboeck, Andreas; Kugi, Andreas
Abstract: An accurate low-order three-dimensional mathematical model for the reheating process in a batch-type industrial furnace for sintered molybdenum plates is derived. The furnace is described as a distributed-parameter system and discretized with the finite volume method. The system parameters are identified from measurement data and the order of the finite volume model is reduced by means of proper orthogonal decomposition. Special attention is paid to the calculation of exit temperatures, required reheating times, and the uncertainty of the surface emissivity of the plates. The derived model facilitates fast and accurate calculation of temperature profiles in the plate and is thus suitable for online applications, such as parameter and state estimation, model predictive control, and production planning.